(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2013)
The appalling prospect of state regulation of therapy was defeated but the bureaucratisation continues, encroaching all the time on our therapeutic freedom. Emotional suffering is relentlessly medicalised, defined as ’mental illness’. The defence of therapy as a place for fearless speech is all the more important in these troubled times.